Penyuluhan dan Pelatihan Diversifikasi Produk Olahan Cabai Pada Kelompok Wanita Tani “Larasati” Desa Andongsari, Ambulu, Kabupaten Jember - Kustiari, Tanti; Fidi Astutik, Diar (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The purpose of community service activities, the Larasati Women Farmers Group (KWT) is able to process chilies, diversify processed products, obtain added value, and be able to market processed chili products. Community service activities was carried out at KWT Andongsari Village, Ambulu District, Jember Regency in September - November 2022. The methods used are lectures, discussions, method demonstrations. The results of the activity obtained chili processed products in the form of various types of chili sauce with the criteria of being safe for consumption, hygienic production processes, adjusted to market tastes. Sambal production deserves to be a prospective business for women farmer groups with a home industry scale